Behaviour Management of the Contemporary Child in Paediatric Dentistry: An Overview of the Research - Mylena Vieira da Silva; Sandra Kalil Bussadori; Elaine Marcílio Santos; Karla Mayra Rezende (Association of Support to Oral Health Research (APESB), 2021)
Objective: To provide an overview of the most relevant studies on non-pharmacological behaviour management techniques for contemporary children, the so-called alpha generation, who undergo dental treatment. Material and Methods: A systematic search was performed on the Medline/PubMed and Google Scholar (grey literature) databases. The articles were read and data collected by two reviewers on an independent basis. Two reviewers collected data from the studies selected in tables structured by using the Rayyan QCRI software. The following data were extracted: year of study, child's age, child's gender, technique used. Results: A total of 322 articles were found, remaining only 17 after duplicates were removed and inclusion and exclusion criteria applied. The studies were conducted between 2010 and 2019 in Saudi Arabia, Greece, India, Brazil, USA, Italy, and Switzerland. The samples ranged from 15 to 306 children aged between 3 and 10 years old. The children attended the dental office for different reasons, ranging from simple prevention to endodontic treatment under local anaesthesia. Several behaviour modification methods are known to be used before and during a dental consultation. Conclusion: After reading the articles, we concluded that alpha generation children are inserted in a daily environment of modernization and that conventional non-pharmacological techniques using technology, such as audio-visual glasses, are more interesting and make children distracted and relaxed during dental treatment, thus minimizing their stress, anxiety and fear.